Day-case cataract surgery. Issue 5 (May 1983) - Ingram, R M; Banerjee, D; Traynar, M J; Thompson, R K
Abstract : The results of 501 day-case cataract extractions are presented. This is a safe way to manage an operation for which there will be an increased demand. Only 13% of these patients stated that they would have preferred to stay in hospital after surgery.